Estimation of Belowground Carbon Stocks in Peatlands under Different Land Cover Types in Ogan Komering Ilir Regency, Indonesia - Rini Endang Pratiwi; Momon Sodik Imanudin; M. Umar Harun (Universitas Muhammadiyah Palembang, 2025)
Monitoring subsurface carbon stocks in peat soils is crucial for understanding how different land cover types contribute to carbon storage and climate change mitigation. This study aims to estimate subsurface carbon (CO₂) stocks in peatlands under various land cover conditions. Soil sampling was conducted three times in October, November, and December 2024 across managed oil palm, unmanaged oil palm, shrubland, and swamp forest land covers. Additional sampling was carried out in August, September, and October 2025 on mixed gardens and secondary forests with dense vegetation. Samples were collected based on peat decomposition levels at an approximate depth of ±400 m and analyzed in the laboratory to determine bulk density (BD) and organic carbon content (%C) using the Loss on Ignition (LOI) method. Carbon stock values were calculated and converted to CO₂ equivalents to obtain total estimates for each sampling point. Data were analyzed descriptively and statistically using One-Way ANOVA followed by the Tukey HSD post hoc test. The results revealed that managed oil palm land had the highest carbon stock 11,607.54 tons/ha, followed by unmanaged oil palm 11,107.32 tons/ha, shrubland 7,691.36 tons/ha, mixed garden 7,510.39 tons/ha, secondary forest 7,415.11 tons/ha, and swamp forest 6,872.56 tons/ha. These findings suggest that land cover type and management practices significantly affect subsurface carbon stocks, with well-managed lands tending to store higher amounts of carbon compared to natural or unmanaged areas.